Reflecting on the research encounter for people in the early stages of dementia: Lessons from an embedded qualitative study. (November 2020) - Abendstern, Michele; Davies, Karen; Poland, Fiona; Chester, Helen; Clarkson, Paul; Hughes, Jane; Sutcliffe, Caroline; Challis, David
Gathering meaningful data from people with dementia presents challenges to researchers involved in both qualitative and quantitative studies. Careful planning and implementation are required, including skilful and sympathetic management by the researcher who must pay attention to the cognitive challenges experienced by the person with dementia. These challenges are particularly evident when conducting structured interviews using standardised measures. This paper presents the findings of an embedded qualitative study undertaken within a pragmatic randomised controlled trial. The novel method involves nesting a qualitative analysis within a quantitative study by recording incidental conversation during structured interviews, requiring no additional data collection. The method shone a light on the formal interview process itself, something rarely revealed outside the interview setting. It provided a unique insight into the challenges posed by research participation for people in early-stage dementia. Analysis revealed three main themes relating to dementia as a condition and to the research design. First, people with dementia contributed very few conversational comments during the structured interviews. Second, the context of the interview, that is: managing the conversational interchange, responding to direct and often sensitive questions and making decisions about day-to day-feelings and experiences was difficult for participants to manage. Third, people in early stage dementia struggled with the content of the structured interviews due to their linguistic and cognitive demands. The findings raise questions about how people with dementia are included in research and the methods employed to gather accurate data with minimal inconvenience and stress for research participants.